ETIOLOGY AND DENTAL STATUS IN PATIENTS WITH DENTITION DEFECTS IN THE RESIDENTS OF THE TRANSCARPATHIA - Klytinska, Oksana; Martyts, Yurii; Dunec, Roman; Tymchak, Vasyl (Eastern Ukrainian Medical Journal, 2024)
The aim of the study. To evaluate the dental status of patients with dentition defects, residents of the Transcarpathia, and to establish the causes of their occurrence. Materials and methods. The dental status was determined in 450 middle-aged people, residents of the Transcarpathia. The etiology of dentition defects was established, and an index assessment of hygiene, inflammatory and destructive changes in the periodontium, resorption of alveolar processes, and bone type was performed. The mathematical analysis and verification of the results, as well as the calculation of the arithmetic mean and standard errors were performed using the Statistica 6.0 software. Results and discussion. In the case of bounded edentulous spaces of 1–2 adjacent teeth, complicated caries prevailed in the etiology in 57.0 %; in the case of bounded edentulous spaces of 3 or more adjacent teeth, periodontal tissue diseases prevailed in 58.0 % (25.8 % – 16 in the upper jaw, 32.2 % – 20 in the lower jaw). In free-end edentulous spaces, periodontal tissue diseases prevailed among the etiologic factors: unilateral – in 75.0 %, bilateral – in 79.4 %. The hygiene was not satisfactory, the presence of moderate and severe gingivitis and periodontitis was observed with the prevalence of D2 bone type in 53.3 % of patients with bounded edentulous spaces, and 54.5 % of patients with free-end edentulous spaces. Conclusions. In the middle-aged adult population of the Transcarpathia, bounded edentulous spaces account for 26.6 %, and free-end edentulous spaces account for 73.4 %.